Quantitative Detection of Proteins by [Co(NH3)6]3+-DNA Probe of Resonance Light Scattering Technique - Li, Y.K. (Asian Journal of Chemistry, 2013)
[Co(NH3)6]3+-DNA complex produces strong electrical force with proteins, which results in strong enhancement of resonance light scattering intensity. Resonance light scattering intensity at 346 nm was proportional to the concentration of bovine serum albumin in the range of 0.05-1.3 μg/mL. The limit of determination for bovine serum albumin has obtained at nanogram level. The method is applied to the assay of bovine serum albumin and good results have been obtained compared with custom measure methods. A sensitive, accurate and convenient new analysis method for micro-determination of proteins is established.